PENERAPAN KONSEP BALANCED SCORECARD DALAM PENGUKURAN KINERJA INSTANSI PEMERINTAH PADA INSTITUT PEMERINTAHAN DALAM NEGERI - rasidi rasidi; Rudi Sadmoko (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2019)
Performance in the public sector is multidimensional and comprehensive, so that the nature of output produced by the public sector is more intangible output, so to measure the performance of the public sector it is necessary to choose a comprehensive performance measurement technique that is the Balanced Scorecard. Research Objectives to describe the application of each Balanced Scorecard perspective in measuring agency performance. The research method used is descriptive qualitative method. IPDN is a public sector organization with a main focus on output that is